2018
DOI: 10.1080/17538963.2018.1453103
|View full text |Cite
|
Sign up to set email alerts
|

The role of China’s household registration system in the urban-rural income differential

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Existing studies have found that the hukou policy leads to low educational attainment among the rural population (Liu 2005) and low cognitive task performance of rural migrant students (Afridi et al 2015). It also creates wage discrimination in the labor market (Meng and Zhang 2001;Démurger et al 2009;Meng 2012;Zhu 2016;Zhang et al 2016;Boffy-Ramirez et al 2018), hinders labor mobility (Bosker et al 2012), and causes productivity losses (Au and Henderson 2006). Our research provides insight into how the hukou policy affects households' housing tenure choice and in turn, wealth inequality in urban China.…”
Section: Introductionmentioning
confidence: 76%
“…Existing studies have found that the hukou policy leads to low educational attainment among the rural population (Liu 2005) and low cognitive task performance of rural migrant students (Afridi et al 2015). It also creates wage discrimination in the labor market (Meng and Zhang 2001;Démurger et al 2009;Meng 2012;Zhu 2016;Zhang et al 2016;Boffy-Ramirez et al 2018), hinders labor mobility (Bosker et al 2012), and causes productivity losses (Au and Henderson 2006). Our research provides insight into how the hukou policy affects households' housing tenure choice and in turn, wealth inequality in urban China.…”
Section: Introductionmentioning
confidence: 76%
“…China’s hukou registration system consists of two broadly recognized residency statuses—urban (non-agricultural) and rural (agricultural)—which serve to regulate internal migration and labor distribution. Hukou status also regulates multiple aspects of an individual’s life including opportunities for employment, education, and access to social benefits and public resources, such as health care, housing, and entitlement programs (Boffy-Ramirez & Moon, 2018; Zhou & Cheung, 2017; Zhu & Österle, 2017). Chinese citizens inherit their initial hukou status from their parents at birth, while it is possible to change from a rural to urban hukou status with considerable administrative barriers.…”
Section: Methodsmentioning
confidence: 99%
“…China's hukou registration system consists of two broadly recognized residency statuses-urban (non-agricultural) and rural (agricultural)-which serve to regulate internal migration and labor distribution. Hukou status also regulates multiple aspects of an individual's life including opportunities for employment, education, and access to resources, such as health care, housing, and entitlement programs [37,38,39]. Chinese citizens inherit their initial hukou status from their parents at birth; it is possible to change from a rural to urban hukou status with considerable policy requirements.…”
Section: Participant Characteristicsmentioning
confidence: 99%